Quantitative proteomic analysis of temporal lysosomal proteome and the impact of the KFERQ-like motif and LAMP2A in lysosomal targeting. Issue 11 (2nd November 2021) - Kacal, Merve; Zhang, Boxi; Hao, Yuqing; Norberg, Erik; Vakifahmetoglu-Norberg, Helin
ABSTRACT: Autophagic pathways are regulated mechanisms that play important roles in lysosome-mediated cellular degradation. Yet, the contribution of different autophagic pathways in lysosomal targeting, and characterization of the extent and specificity in their degradome remains largely uncharacterized. By undertaking a multiplex quantitative mass spectrometry approach, we have previously analyzed the lysosomal proteome during chaperone-mediated autophagy (CMA)-stimulated conditions in cancer cells. Here, we have extended our multiplex quantitative mass spectrometry and bioinformatics analysis on the proteome from isolated lysosomes to gain a comprehensive view of the temporal enriched lysosomal content upon non-macroautophagy-activated conditions. In parallel, we describe the functional dependency of LAMP2A on, and to what degree the presence of KFERQ-like motifs in proteins influences, their lysosomal targeting. These findings establish a framework for a better understanding of the degradome mediated by autophagic pathways beyond macroautophagy, and present characterization of the impact of LAMP2A in lysosomal targeting in cancer cells. Abbreviations : CMA: chaperone-mediated autophagy; ER: endoplasmic reticulum; EIF4A1: eukaryotic translation initiation factor 4A1; eMI: endosomal microautophagy; FC: fold change; GO: gene ontology; ISR: integrated stress response; LAMP2A: lysosomal associated membrane protein 2A; MA: macroautophagy; MI: microautophagy; MS: mass spectrometry; PCA: principal component analysis; TAX1BP1: Tax1 binding protein 1.